2021
DOI: 10.3389/fphar.2021.797605
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of AOM/DSS-Induced Murine Colitis-Associated Cancer by Evodiamine Intervention is Primarily Associated with Gut Microbiota-Metabolism-Inflammatory Signaling Axis

Abstract: Evodiamine (EVO), an indole alkaloid derived from Rutaceae plants Evodia rutaecarpa (Juss.) Benth.、Evodia rutaecarpa (Juss.) Benth. Var. bodinieri (Dode) Huang or Evodia rutaecarpa (Juss.) Benth. Var. officinalis (Dode) Huang, has anti-inflammatory and anti-tumor activities. Our previous study found that EVO attenuates colitis by regulating gut microbiota and metabolites. However, little is known about its effect on colitis-associated cancer (CAC). In this study, the protective effects of EVO on azoxymethane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 63 publications
2
20
0
Order By: Relevance
“…The bacterial family Erysipelotrichaceae belongs to the Firmicutes phylum. Studies have revealed the increased abundance of Erysipelotrichaceae in CRC patients and the DMH induced colon cancer animal model [28,42,43], implying that it may be involved in the occurrence and development of CRC. Few research studies have investigated the relationship between Desulfovibrionaceae and CRC, however, many studies reported that it is an endotoxin-producer [44][45][46], endotoxin can promote colorectal cancer cells adhesion and invasion through the regulation of the TLR4/NF-κB pathway [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial family Erysipelotrichaceae belongs to the Firmicutes phylum. Studies have revealed the increased abundance of Erysipelotrichaceae in CRC patients and the DMH induced colon cancer animal model [28,42,43], implying that it may be involved in the occurrence and development of CRC. Few research studies have investigated the relationship between Desulfovibrionaceae and CRC, however, many studies reported that it is an endotoxin-producer [44][45][46], endotoxin can promote colorectal cancer cells adhesion and invasion through the regulation of the TLR4/NF-κB pathway [47].…”
Section: Discussionmentioning
confidence: 99%
“…Some inflammatory cytokines such as IL-1, IL-6, IFNγ and TNFα play an importa role during the development of CAC. Studies showed an increased level of these cyt kines in AOM/DSS induced mice serum or colon [25][26][27][28].…”
Section: Pc Reduces the Level Of Proinflammatory Cytokines In Cac Micementioning
confidence: 98%
“…var. bodinieri (Dode) Huang (Nam et al, 2016;Wang et al, 2021). EF belongs to Rutaceae family, Tetradium ruticarpum (A.…”
Section: Source Materialsmentioning
confidence: 99%
“…Dehydroevodiamine (DHE,3':3,4]pyrido[2,1-b]quinazolin-14-ium-13-ide, Figure 1A), molecular formula: C 19 H 15 N 3 O, PubChem CID: 9817839, CAS NO. 67,909-49-3, relative molecular mass: 301.3 (https://pubchem.ncbi.nlm.nih.gov/compound/9817839), is one of the natural bioactive components derived from a widely used traditional Chinese medicine (TCM), Evodiae Fructus (EF, Wuzhuyu in Chinese, Rutaceae family) (Figure 1B) (Park et al, 1996;Nam et al, 2016;Wang et al, 2021). For thousands of years, EF has been widely used as a central agent in classical Chinese herbal prescriptions (Wuzhuyu decoction and Zuojin formula) to treat migraine (known as "Jueyin headache" in ancient China) as well as other diseases (Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many herbal medicines, such as Ganoderma Lucidum , American Ginseng, Red Ginseng, Gynostemma Pentaphyllum , and Curcumin, significantly inhibit the growth of pathogenic bacteria such as Clostridium , Escherichia , Staphylicus , Verrucomicrobia but increase the number of probiotic Bifidobacteria and lactobacilli , resulting in the increased diversity of the gut microbiota in DSS-induced CRC mouse model ( Guo et al., 2015 ; McFadden et al., 2015 ; Yu et al., 2015 ; Chen et al., 2016 ; Wang et al., 2016 ; Gong et al., 2019 ; Lv et al., 2019 ; Jiang et al., 2020 ; Shen et al., 2020 ; Sui et al., 2020 ; Sun et al., 2020 ; Zhang et al., 2020 ; Hao et al., 2021 ; Wang et al., 2021 ; Zhang et al., 2021 ; Zhu et al., 2021 ). These anti-CRC profiles of herbal medicine on gut microbiota are summarized as shown in Table 1 .…”
Section: Herbal Medicine Gut Microbiota and Colorectal Cancermentioning
confidence: 99%